2005
DOI: 10.1007/s15010-005-5064-6
|View full text |Cite
|
Sign up to set email alerts
|

Aortitis Diagnosed by F–18–Fluorodeoxyglucose Positron Emission Tomography in a Patient with Syphilis and HIV Coinfection

Abstract: The most common manifestation of cardiovascular syphilis, a rare diagnosis since the introduction of penicillin, is aortitis of the ascending aorta. Since the majority of patients with uncomplicated aortitis are asymptomatic, early diagnosis is difficult. We report the case of an HIV-positive patient with asymptomatic syphilitic aortitis that was incidentally diagnosed with F-18-fluorodeoxyglucose (FDG) positron emission tomography (PET). We conclude that FDG-PET could become a promising new imaging technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…In 2005, Kosters et al reported a case of widespread lymphadenopathy and aortitis in a participant with early syphilis infection co-infected with HIV using PET scan imaging 8. Kosters et al suggested that early aortic involvement might occur more often than thought, which is supported by the findings in our study.…”
Section: Discussionsupporting
confidence: 85%
“…In 2005, Kosters et al reported a case of widespread lymphadenopathy and aortitis in a participant with early syphilis infection co-infected with HIV using PET scan imaging 8. Kosters et al suggested that early aortic involvement might occur more often than thought, which is supported by the findings in our study.…”
Section: Discussionsupporting
confidence: 85%
“…• AIDS-associated opportunistic infections, associated tumors, and Castleman disease (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83).…”
Section: Common Clinical Indicationsmentioning
confidence: 99%
“…In secondary syphilis inflammation has been previously described in association with hepatitis, uveitis, meningitis, and two cases of aortitis. [2, 3] Aortitis, if left untreated, can result in aortic root dilation could result in aortic insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators recently reported an incident finding of widespread syphilitic lymphadenopathy in early syphilis by PET scan [3]. Other reports have suggested that PET scans may be promising techniques for both diagnosis and follow–up of patients with syphilitic aortitis [2-4].…”
Section: Discussionmentioning
confidence: 99%